Life cycle assessment of Brazilian bleached eucalyptus kraft pulp: Integrating bleaching processes and biogenic carbon impacts - Rhonald Ortega; Naycari Forfora; Isabel Urdaneta; Ivana Azuaje; Keren A. Vivas; Ramon E. Vera; Jorge Franco; Ryen Frazier; Camilla Abbati; Daniel Saloni; Hasan Jameel; Richard Venditti; et al. (Cleaner Environmental Systems)
Bleached eucalyptus kraft (BEK) pulp dominates global pulp production, yet the environmental impacts of its bleaching sequences in Brazil are not fully explored. Addressing this gap, we conducted a comparative life cycle assessment (LCA) of three bleaching sequences: conventional elemental chlorine-free (ECF), ECF with oxygen delignification, and ECF with oxygen delignification plus acid washing. We estimated the average global warming potential (GWP) for BEK delivered to the U.S. and examined how forest carbon cycle (FCC) elements, specifically biogenic GWP (GWPbio) and potential soil organic carbon (SOC) sequestration, influence GWP outcomes. Results show that the ECF sequence with oxygen delignification and acid washing reduces GWP by 11% and outperforms conventional ECF in 10 out of 11 environmental impact categories. The average GWP for Brazilian BEK delivered to the U.S. is 576 kg CO₂-eq/ton. Sensitivity analyses demonstrate that adding GWPbio increases GWP by 18%, whereas accounting for potential SOC sequestration reduces it by 39%. These findings highlight the necessity of optimizing bleaching processes and developing a standardized BEK LCA model for comparing the environmental impact of different fibers. This work sets a precedent for integrating FCC elements into LCAs and underscores the potential of SOC sequestration in mitigating climate change impacts.